Factorial Study Of The Importance Of Some Flexibility and Muscular Strength With the Shape Of The Body For Badminton Players - dawed, Thaer; Nabhan, Nada (Journal of Physical Education, 2010)
Physical traits and body measurements are considered that base for testing athletes according to their sport. It is said that however good the coaches' abilities they can't make a champion without the athlete having the proper physical traits and body measurements suitable for that sport. The importance of the research lies in identifying some forms of muscular strength and flexibility as well as the unique body shape of badminton players. The aims of the research is to specify the physical abilities tests and body measurements as factors suitable for labeling as well as identifying the factorial aspect of physical tests and body measurements for badminton players. The research was applied on (50) badminton players of the ages (14 – 16 years) from 15 athletic clubs of the season 2008 – 2009.The research included (9) physical tests for measuring power defined by speed and explosive power and (15) body measurements. Factorial analysis was used to conclude (8) factors. The variables of the research were as follows; the first factor thigh and lower limb index, lower limb, trunk width index, the second factor sitting from laying position (30 sec), from standing position and flexing and extending the knees (20sec), skeleton index (20), third factor trunk bender from standing position, forth factor, wide jump, medicine ball pushing with the hands (3kgm) and chest height).Finally the researchers came up with a set of conclusions and recommendations.